A validation study of the facilitator assessment instrument at the De La Salle-College of Saint Benilde School of Professional and Continuing Education - Mones, Reynaldo A. (Animo Repository, 2005)
The study evaluates the results of the facilitator evaluation in diploma or post baccalaureate programs. The research used correlation and factor analysis as the statistical tools to evaluate an assessment instrument. This study, initially aimed to evaluate the data in terms of its ability generate some information that would help in developing and designing new programs and its marketing, revealed the need to review the instrument and the process involved in its administration.